Efek Serbuk Jahe Merah (Zingiber Officinale Var Rubrum) Terhadap Penurunan Intensitas Dismenore Pada Siswi SMAN 1 Muncang Kabupaten Lebak Banten : The Effect of Red Ginger Powder (Zingiber Officinale Var Rubrum) on Reducing the Intensity of Dysmenorrhea in Female Students of SMAN 1 Muncang, Lebak Regency, Banten - Awalia, Lieska (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Dysmenorrhea is a condition that occurs during menstruation or menstruation which can interfere with activities and requires treatment which is characterized by pain or pain in the abdominal or pelvic area "(Judha 2012)", Dysmenorrhea is pain during menstruation that interferes with women's daily activities. According to WHO (2012), there were 1,796,425 people (90%) experiencing dysmenorrhea with 10-15% experiencing severe dysmenorrhea. About 75% of women report some degree of discomfort related to menstruation, and about 15% report severe dysmenorrhea.  Methods: The research method is a pre-experimental research design. In this study, the authors conducted quantitative research using the pre-experimental design method, type one group pretest-posttest (preliminary test, final test, single group). Sampling was carried out by purposive sampling and in this study the samples were partially taken from the entire object studied and considered to represent the entire population of class X, X1, and XII students at SMAN 1 Muncang in the year 2022/2023 who experienced dysmenorrhea as many as 56 people.  Results: The results of the Wilcoxon test showed that the p-value of red ginger was 0,000 0,05 so there was an effect of giving red ginger. The experimental group was given capsules containing red ginger powder 4x1 for 2 days at a dose of 250 mg. The results of the independent t-test obtained a p-value of 0,000 (α 0,05).  Discussion: Broadly speaking, there is an effect of red ginger powder (Zingiber officinale var. Rubrum) on reducing the intensity of dysmenorrhea pain in female students at SMAN 1 Muncang, Lebak Regency Banten before and after consuming red ginger powder (Zingiber officinale var. Rubrum) as evidenced by the results of statistical tests using One-Sample Statistics with a significance value of p 0,000.